Implementation of School Culture-Based Character Education: A Multi-Site Study at SMA IT Darul Istiqamah Maros and SMAS Buq’atun Mubarakah Makassar - Zulfitri; Arismunandar; Wahira (International Journal of Education, Vocational and Social Science, 2025)
This study aims to describe and analyze the implementation of school culture-based character education through a multi-site study at SMA IT Darul Istiqamah Maros and SMAS Buq’atun Mubarakah Makassar. The focus of this research includes the primary character values being developed, the strategies for implementation, and the challenges encountered. This research utilizes a qualitative approach with a multi-site study design. Data was collected through observation, in-depth interviews, and documentation. The informants in this study included school principals, teachers, and students. The results of the study show that both schools focus on developing the character values of being religious, disciplined, independent, and responsible. Implementation strategies are dominated by the instillation of theory, modeling, and structured routine habituation. These strategies are proven effective in shaping student character; however, the implementation faces internal challenges such as the diversity of student backgrounds and the commitment of teachers , as well as external challenges including the influence of outside culture, particularly from gadgets, and a lack of consistent support from parents. This study concludes that the effectiveness of character education is highly dependent on the synergy of internal strategies and the ability to mitigate external challenges.